Enhanced visible‐light activity of Ti3+ self‐doped TiO2 with co‐exposed 001 and 101 facets. (1st April 2018) - Li, Junqi; Niu, Lijun; He, Xuanmeng
Abstract : The Ti 3+ self‐doped titanium dioxide (TiO2 ) nanosheets with co‐exposed 001 and 101 facets were successfully synthesised by the one‐step solvent thermal method. The as‐prepared samples were characterised by X‐ray diffraction, transmission electron microscopy, X‐ray photoelectron spectroscopy (XPS) and diffuse reflectance spectroscopy. The results showed that the Ti 3+ self‐doped TiO2 nanosheets with anatase structure exposed 001 and 101 facets. XPS spectra confirmed Ti 3+ were self‐doped TiO2 nanosheets, and which narrowed the band gap of TiO2 . Comparing to bare TiO2, the Ti 3+ self‐doped TiO2 nanosheets exhibited excellent photocatalytic activities. The reasons were that the co‐exposed 001 and 101 crystalline facet effectively improved the separation efficiency of photogenerated electron–hole pairs, and the existence of Ti 3+ and oxygen vacancy resulted in a narrowing band gap and enhancing visible absorption.